2011
DOI: 10.1007/s00535-011-0515-6
|View full text |Cite
|
Sign up to set email alerts
|

Oral symptoms including dental erosion in gastroesophageal reflux disease are associated with decreased salivary flow volume and swallowing function

Abstract: Oral symptoms in GERD are likely to be associated with impaired salivary flow volume or swallowing function. Treatment for the oral dryness induced by reduced salivary flow volume and rehabilitation for swallowing function could be indicated in patients with GERD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
85
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(95 citation statements)
references
References 31 publications
6
85
1
3
Order By: Relevance
“…Maintaining a sufficient amount of saliva is effective for preventing dental caries and improvement of oral symptoms in gastroesophageal reflux disease (GERD) [37]. However, the present study showed no significant difference in the rate of change in the amount of saliva or in the rate of change in salivary pH before and after the use of the active agent between patients who responded and those who did not respond to the agent.…”
Section: Discussioncontrasting
confidence: 54%
“…Maintaining a sufficient amount of saliva is effective for preventing dental caries and improvement of oral symptoms in gastroesophageal reflux disease (GERD) [37]. However, the present study showed no significant difference in the rate of change in the amount of saliva or in the rate of change in salivary pH before and after the use of the active agent between patients who responded and those who did not respond to the agent.…”
Section: Discussioncontrasting
confidence: 54%
“…To resolve this issue, the influence of therapy for periodontitis on GERD prevalence should be investigated in collaboration with dentists in a future study. Several investigators have reported that dental erosion is correlated with the prevalence of GERD (24)(25)(26)(27). Therefore, the relationship with GERD associated dental erosion is considered to be different than that between GERD and periodontitis, though those may have some effect on each other.…”
Section: Discussionmentioning
confidence: 99%
“…In addi-tion, periodontitis may induce or worsen GERD, since saliva secretion, which is influenced by oral hygiene including the periodontal status, has been demonstrated to be associated with GERD (21)(22)(23). Reflux of the gastric acidic contents into the oral cavity may also affect the local bacterial flora and the status of periodontitis, since several investigators have reported a close correlation between dental erosion and gastroesophageal acid reflux (24)(25)(26)(27). However, the relationship between periodontitis and GERD has not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…Oral problems arising as a direct result of GERD include tooth erosion and halitosis [5,[25][26][27]. Tooth erosion is thought to result from the acidity of the gastric contents that reach the mouth during repeated GERD episodes, especially if they are inadequately buffered by saliva [28,29].…”
Section: Introduction Backgroundmentioning
confidence: 99%